Heterogeneity of Indonesian primary school students’ mathematical critical thinking skills through problem-based learning: A meta-analysis - Nugraha, Trisna; Suparman, Suparman (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
The synthesis of some empirical researches revealed that the implementation of problem-based learning (PBL) has a heterogeneous effect size on the mathematical critical thinking skills (MCTS) of primary school students in Indonesia. However, it seems that no researches were investigating the causative factors of the heterogeneity of primary students’ MCTS through PBL. Therefore, this meta-analysis research was employed to examine three potential factors that were PBL class capacity, PBL treatment duration, and mathematics topic predicted as the causative factors of the heterogeneity of primary students’ MCTS. The Q Cochrane test by using the Comprehensive Meta-Analysis (CMA) application was used to examine these potential factors. The synthesis of ten primary studies published in 2015 – 2020 and indexed by Scopus, Google Scholar, Sinta, and Web of Science, showed that PBL treatment duration and mathematics topic were the significant factors causing the heterogeneity of primary students’ MCTS. However, PBL class capacity was not a significant factor causing the heterogeneity of primary students’ MCTS. Thus, primary school mathematics teachers should consider PBL treatment duration established and mathematics topics selected in cultivating primary students’ MCTS by implementing PBL.